The prospects ability of contemporary epistemology for signification internal construction of plastic artwork (Al-Academy, 2022)
Based on the systematic scientific investigation of artistic achievement, researchers (critics) adhere to mechanisms based on epistemology, through which it is envisaged to reveal the meaning of the achievement as the product of three actors: the effectiveness of an artistic sense, the effectiveness of an idea, and the arousal of taste according to systematic criticism procedures that investigate the new artistic achievement. Or, in a specific way, the possibility of meaning in all the accomplished from the aesthetics of artistic presentation and the character of the self-accomplished by the "artist" and the critic invokes his critical tools with certain cognitive foundations. In defining its nature from the rest of the other cultural achievements, including the applied, art is a product that investigates its presence in a free open space between reality, feeling and awareness, and in an individual “special” way to express the enjoyment of a new idea. Awareness of the artist These two factors contribute to the formation of the new art icon as a new presence in what we clearly feel in the characteristic of creativity